Adsorption of natural gas and hydrogen on Cu3(btc)2 - Mohd Zoehdi, Ramli (2009)
Metal organic framework (MOFs) is capable of storing large amount of gases. Cu3(btc)2 is one of the most promising storage materials. The purpose of this research is to develop and characterize the adsorbent, Cu3(btc)2 as a storage of the methane and hydrogen for NGV and fuel cell application at room temperature and at low pressure. The methane and hydrogen adsorption into the metal organic frameworks was examined with two different parameters; pressure and time of adsorption. For the methane, the pressure were used are 2.0 bars, 1.5 bars and 1.0 bars. Meanwhile, for the hydrogen, the pressure were used are 6.0 bars, 4 bars and 2.0 bars. The time of adsorption that were used for methane and hydrogen are 1 hour, 2 hours, 3 hours and 4 hours respectively. The result of the experiment showed that the weight of Cu3(btc)2 sample after the adsorption with hydrogen was decreased. Or in other word, the Cu3(btc)2 sample did not adsorb hydrogen or adsorbed the hydrogen in very small quantity. This is because hydrogen only adsorb on Cu3(btc)2 at lower temperature which is 77K(-196˚C). The second reason was the Cu3(btc)2 sample was not crystallized as there was no proper autoclaves to synthesis sample at 393 K and 12 hour. For the methane adsorption on Cu3(btc)2, the weight of the sample after adsorption was increased. Hence, this proved that Cu3(btc)2 can absorb the methane. However, the percentage of increased weight of the sample was quite low. This was due to the pressure that were used for methane adsorption on Cu3(btc)2 were very low which are from 1.0 bar to 2.0 bar only. The characteristic of Cu3(btc)2 was examined using Scanning Electron Microscope (SEM) to observe the structure of the metal alloy before and after adsorption. From the observation, it is showed that the adsorption was occurred in the Cu3(btc)2 as the sample structure was expanded and the small pore of the sample was decreased. As a conclusion, the pressure and temperature of adsorption, pore size and surface area of sample are the essential parameter for the adsorption.